2003
DOI: 10.1088/0953-8984/15/37/006
|View full text |Cite
|
Sign up to set email alerts
|

Raman and x-ray diffraction studies of nanometric Sn2P2S6crystals

Abstract: Nanometric Sn2P2S6 crystalline powders and ceramics are studied by x-ray diffraction and Raman spectroscopy. The average crystallite size is estimated from TEM and x-ray data. The observed features in the Raman spectra are discussed in view of confinement-related selection rules relaxation, surface phonon modes and possible partial substitution of sulfur by oxygen at the nanometric powder surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Besides, the maxima at 142, 183, and 244 cm . Note that the frequency positions of all these bands correlate with the known Sn 2 P 2 S 6 phonon spectrum [9] as well as with our earlier measurements for Sn 2 P 2 S 6 micro-and nanopowders and ceramics where features near 85, 140, 185, 245, 260, and 290 cm −1 were observed [22]. The observed features clearly confirm Sn 2 P 2 S 6 crystallite formation in the glass matrix under annealing.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Besides, the maxima at 142, 183, and 244 cm . Note that the frequency positions of all these bands correlate with the known Sn 2 P 2 S 6 phonon spectrum [9] as well as with our earlier measurements for Sn 2 P 2 S 6 micro-and nanopowders and ceramics where features near 85, 140, 185, 245, 260, and 290 cm −1 were observed [22]. The observed features clearly confirm Sn 2 P 2 S 6 crystallite formation in the glass matrix under annealing.…”
Section: Resultssupporting
confidence: 87%
“…The slight difference in frequency can evidently be explained by the different long-range environment somewhat distorting the rings under consideration. It should also be mentioned that in our earlier study of Sn 2 P 2 S 6 nanocrystals obtained by ball milling we observed the weak band centred at 406 cm −1 , assumed to stem from partial S→O substitution in PS 3 pyramids due to oxidation at the nanocrystal surface [22]. The band of similar frequency at 411 cm −1 was observed in the Raman spectra of Sn 2 P 2 S 6 crystals recovered after highpressure treatment, where it was possibly related to pressure-induced defects [39].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The nanoparticles were prepared by milling microparticles of SPS, and then separately BaTiO 3 , ͑Х1 m size͒, with oleic acid for 100 h. The expected size of nanoparticles was of the order of 10 nm, based on the published transmission electron microscopy ͑TEM͒ images of SPS powder after 25-75 h of milling. 11 However, while those TEM images allowed some important size characterization of nanoparticles, their shape and distribution was difficult to resolve in detail. Recently, high-resolution images of BaTiO 3 nanocrystals, using AFM in tapping mode, were published 12 and, therefore, in our analysis, we opted for this technique.…”
Section: Ferroelectric Nanoparticles In Low Refractive Index Liquid Cmentioning
confidence: 99%
“…For each of the compounds microcrystalline powders of various grain size were obtained by ball milling the material in a stainless steel cylindrical vial, depending on the milling process duration. Transmission electron microscopy and X-ray diffraction showed that the finest powder fractions obtained after 75-h and 50-h milling contained near-spherical Sn 2 P 2 S 6 nanocrystals with average size down to 9 nm [7] and rod-shaped SbSI crystallites with transverse size down to 70 nm and length 0.5-1 µm [8]. Hence, SbSI appeared to be much harder in the course of attrition and to preserve the rod-like shape typical for the bulk single crystals of this compound what is quite consistent with the chain-like structure of SbSI.…”
Section: Methodsmentioning
confidence: 99%